Legal Regulation of Building Energy Efficiency and Housing Rights: Balancing Sustainability and Social Justice - Kudeikina, Inga; Kaija , Sandra (European Journal of Sustainable Development, 2025)
The European Union has set ambitious climate and sustainability goals, which include stringent energy efficiency requirements for buildings. The Energy Efficiency Directive and the Energy Performance of Buildings Directive establish minimum efficiency standards, mandatory renovations, and carbon reduction targets. While these regulations promote environmental sustainability and economic efficiency, they also raise legal and social concerns. A key issue is the proportionality of energy efficiency obligations in relation to property rights. While mandatory renovations serve the public interest by addressing climate change, they impose significant financial burdens on property owners, particularly vulnerable social groups. These requirements may restrict owners' decision-making freedom, raising concerns about compliance costs and potential property devaluation. Moreover, energy efficiency mandates impact housing affordability, potentially exacerbating social inequality. Although energy-efficient homes reduce long-term utility costs, initial renovation expenses can drive up property prices, limiting access to housing for low-income populations. This paper examines the legal implications of the Energy Efficiency Directive and the Energy Performance of Buildings Directive, assessing their proportionality, impact on property rights, and social security risks. It also explores policy recommendations to balance environmental objectives with legal certainty and social justice, ensuring that sustainability measures do not disproportionately burden homeowners or deepen housing inequalities. Keywords: Housing Rights; Legal Regulation of Energy Efficiency; Proportionality; Social Justice; Sustainability